Is there an association between public spending on health and choice of healthcare providers across socioeconomic groups in India? - Evidence from a national sample. (September 2021) - Mulcahy, Patrick; Mahal, Ajay; McPake, Barbara; Kane, Sumit; Ghosh, Prabir Kumar; Lee, John Tayu
Abstract: The role of public spending on health in reducing socioeconomic inequalities in healthcare is an emerging area of research, little supporting empirical evidence is available from low- and middle-income countries. This study examined: (1) the relationship between public spending on health per capita and the decision whether to seek healthcare or not, (2) the relationships between public spending on health per capita and choice of medical provider, and (3) whether these relationships varied by socioeconomic groups in India. Our study utilized the nationally representative 71st National Sample Survey of India, using 26, 142 people who had been ailing in the past 15 days, the survey took place between the 1st of January and June 30, 2014. Two regression-based approaches were used to examine the association between public spending and choice of medical providers: (1) Multilevel multinomial regression; and (2) Instrumental variable regression. We examined the differential impacts of public spending on healthcare utilisation by socioeconomic groups. Increased public spending on health was not associated with changes in ailing people's decision whether to seek care or not (p > 0.05 in all analyses). However, increased public spending on health was associated with reductions in patients choosing private medical providers [adjusted odds ratio = 0.88 (95%CI 0.85–0.91) for outpatient private clinics] compared to outpatient government clinics. These associations may be greater among the lower economic groups compared with their counterparts. Across India, higher levels of government investment in health services are recognised by healthcare users and shown in their pattern of healthcare utilisation. That an increase in public spending on health results in a decrease in the use of private providers, particularly outpatient facilities with no inpatient capabilities, provides strong evidence for the effectiveness of 'regulation by competition'. This is a strong argument for focusing health system strengthening, and strategies for achieving universal healthcare on public investment. Highlights: When public spending on health increased more people used the public system. People's healthcare choices in India supports Regulation by Competition. This provides policy makers a tool to regulate the private market.